Analyzing and Estimating Thermal Conductivity of Sedimentary Rocks from Mineral Composition and Pore Property. (20th March 2021) - Tang, Boning; Zhu, Chuanqing; Qiu, Nansheng; Cui, Yue; Guo, Sasa; Luo, Xin; Zhang, Baoshou; Li, Kunyu; Li, Wenzheng; Fu, Xiaodong
Abstract : In this study, thermal conductivities of 128 rock samples located in the Xiong'an New Area and Tarim Basin were measured using the optical scanning and transient plane source methods. The thermal conductivities of the Xiong'an New Area samples range from 1.14 to 6.69 W/(m·K), in which the mean thermal conductivities of dolomite and sandstone are 4.95 ± 1.19 and 1.80 ± 0.44 W / m · K, respectively. In the Tarim Basin, sandstone samples have thermal conductivities ranging from 1.21 to 3.56 W/(m·K) with a mean value of 2.51 ± 0.66 W / m · K . The results can provide helpful reference data for studies of geothermics and petroleum geology. Calculation correction and water-saturated measurements were conducted to acquire in situ rock thermal conductivity, and good consistency was found between both. Compaction diagenesis enhances bulk thermal conductivity of sedimentary rocks, particularly sandstones, by decreasing the rock porosity and mineral particle size. Finally, correction factors with respect to mineral grains were proposed to correct the thermal resistance of intergrain contacts and degree of intactness of crystals, and an optimized formula was adopted to calculate the thermal conductivity of sedimentary rock based on rock structure and mineral constituents.